Analysis of the Development of Kelong Park Natural Tourism Objects Based on Visitor Perceptions in Kakaskasen Dua Tomohon Village - Kumaat, Hendry; Sangian, Meiske Martha; Rompas, Margrace Diana; Lumare, Mercy Ariane (Indo Consultan Energi, 2025)
Taman Kelong Tomohon is one of the tourism potentials in North Tomohon, Kakaskasen Dua Village, which has beautiful parks, a natural atmosphere, and cool air because it is mountainous. This study aims to analyze the development of the Taman Kelong tourist attraction. This study used a visitor perception survey approach with 30 respondents who were taken randomly based on the shared Google form link. The study found that 76.7% stated that the Taman Kelong tourist attraction has beautiful scenery, a natural atmosphere, and cool air. Furthermore, 60% stated that the fee of Rp25,000 was affordable, and 66.7% answered that the parking area was large. However, it was not the correct answer because the large area of ​​Taman Kelong allowed visitors to park their vehicles outside the parking area provided. 36.7 answered that the food price was affordable, and 53.3% answered that the service provided by the cafe and restaurant servers was friendly. As many as 46.7% answered that they went to the Taman Kelong tourist attraction to travel with their families. As many as 66.7% answered that the attraction of Taman Kelong tourism is its beautiful flower garden, beautiful scenery, and many photo spots. Moreover, 66.7% answered that the maintenance and sustainability of Taman Kelong tourism objects are well maintained. The development of Taman Kelong tourism objects currently focuses on three things, namely expanding the parking area, expanding the pool area to the front of the hotel, which can also be a solution to the smell of the barn from residential areas, and continuing the construction of the Taman Kelong hotel which was stopped because the government had not issued the building permit.